The Influence of Project-Based Learning Models to Increase Student Motivation and Learning Outcomes In Digital Simulation And Communication Subjects In the 3T Region at Vocational School Negeri 4 Talaud - Matandatu, Stevani; Rompas, Parabelem Tinno Dolf; Oroh, Rolly Robert (JR Education, 2023)
The background of this research is that learning is still focused on the teacher. During the ongoing learning process in the classroom, it can be seen that students are not participating enough in learning because students only accept and are passive. There were only a few students who seemed to pay attention to the explanation and respond to questions from the teacher, while some other students were less enthusiastic, less attentive, and interested in following the learning process. This research aims to determine the effect of project-based learning, as well as determine the increase in student motivation and learning outcomes through the application of the project-based learning model. The method used in this research is a quantitative method of the Quasy Experiment type with the Static Group Comparison research design. The population in this study were all class X students at SMK Negeri 4 Talaud. Sampling used the Purposive Sampling technique. Class X Accounting is the experimental class and Class X TITL is the control class. Research data on students' Digital Simulation and Communication learning outcomes was obtained from the final test. Based on the analysis of the research data, it is known that the final test of Digital Simulation learning outcomes was calculated using the t-test with the result t count>ttable (2,731 > 22, which means that H0 was rejected at the α = 0.05 level. So from these results, it can be concluded that rejects H0 and accepts H1. So it can be concluded that the effect of using project-based learning on students' Digital Simulation and Communication learning outcomes is better than students who take conventional learning.